Mode I fracture toughness of glass fibre reinforced thermoplastic composites after UV and atmospheric plasma treatments. (3rd May 2023) - Scarselli, G.; Quan, D.; Prasad, V.; Rao, P.S.; Hardiman, M.; Reid, I.; O'Dowd, N.P.; Murphy, N.; Ivankovic, A.
Abstract: In the present paper, the mode I fracture toughness properties of a thermoplastic composite resin reinforced with glass fibres are experimentally evaluated. The neat resin is initially characterized in terms of static and mode I fracture toughness properties. Then three sets of panels are manufactured and tested: reference panels made of untreated glass fibres and the thermoplastic resin; UV treated glass fibres reinforced thermoplastic panels and plasma treated glass fibres reinforced thermoplastic panels. The effect of the treatment on the interfacial adhesion strength between fibres and matrix is characterized by a push-out test. An overall increase of the interfacial strength leads to an overall decrease of the composite mode I fracture toughness evaluated by Double Cantilever Beam (DCB) tests. Optical and Scanning Electron Microscopy images of the fracture surfaces are acquired and used to obtain a better interpretation of the fracture mechanisms. Graphical abstract: Image 1